Effectiveness of an intervention campaign on influenza vaccination of professionals in nursing homes: A cluster-randomized controlled trial. Issue 10 (28th February 2019) - Borgey, France; Henry, Liliane; Lebeltel, Josiane; Lescure, Pascale; Le Coutour, Xavier; Vabret, Astrid; Verdon, Renaud; Thibon, Pascal
Highlights: Flu vaccination rates are low among healthcare professionals (≈20%) in most countries. Nursing home professionals must be vaccinated for individual + collective protection. Our intervention campaign significantly increased the flu vaccination rate. Campaigns should be repeated every year and simplified in order to be more effective. Abstract: Background: Seasonal influenza has a major individual and collective impact, especially among the elderly living in nursing homes. To prevent infection by influenza viruses, vaccination of residents and professionals is an essential measure. However, while the vaccination rates of residents are generally high (>85%), rates among professionals are generally approximately 20%. To evaluate the effectiveness of an intervention campaign on the improvement of the influenza vaccination rate of professionals, a regional intervention study was proposed for nursing homes during the 2014–15 season. Methods: Cluster-randomized controlled trial (with a nursing home representing a cluster). In the intervention group, a campaign on influenza vaccination was offered to staff, combining different teaching aids in a multimodal approach. In the control group, no intervention was proposed. The primary endpoint was the rate of influenza vaccination among staff. Before and after the study, professionals were asked to complete short questionnaires on their perceptions of influenza vaccination. A multilevel analysis was carried out to compare the vaccination rates between the 2 groups and their evolution before/after the winter period. Results: A total of 32 nursing homes were randomized, and 6 were excluded. Initial vaccination rates were 27.6% in the intervention group and 24.2% in the control group (p = 0.16). After the study, these rates increased to 33.7% and 22.9%, respectively, which was a relative difference of +22.1% in the intervention group compared to −5.4% in the control group, p = 0.0025. Conclusions: Despite professionals' reluctance to be vaccinate, participation in a promotional campaign with a pragmatic approach has increased the rate of influenza vaccination. The approach will be offered to all nursing homes in the region after revision of the tools to enhance their ease of use and pedagogical messages focused on the direct benefits to professionals.